A Analisis Penerapan Strategi Pemasaran Pada Rumah Makan Ikan Bakar Cianjur Denpasar: ANALISIS PENERAPAN STRATEGI PEMASARAN PADA RUMAH MAKAN IKAN BAKAR CIANJUR DENPASAR - Paskalis Apriliano; Dewa Nyoman Sadguna; I Gusti Ngurah Sugiana (Fakultas Pertanian, Universitas Warmadewa, 2023)
Abstract This study aims to determine the marketing strategy that has been implemented so far and the factors that have become obstacles to the Cianjur grilled fish restaurant, the Denpasar branch of the Makassar branch. Sampling in this study was carried out using informant techniques, namely managers who conceptually know and understand the ins and outs of the strategy used and how to market their products, the head of the finance department who handles incoming and outgoing finances, the head of HR (personnel) who knows the quality of work of both employees sales, delivery and cashiers, and took 10 consumers to find out their responses or responses to the Denpasar Branch of the Ikan Bakar Cianjur Restaurant. Data analysis used the SWOT analysis method which includes IFAS and EFAS analysis. The results of the IFAS analysis a value of 2.8 was obtained. This indicates that it has been able to take advantage of its strengths and has been able to overcome internal weaknesses. EFAS obtained a value of 2.7. This indicates that the Denpasar branch of the Cianjur grilled fish house restaurant with respect to the external environment is quite good. From the results of the IE matrix, the strategy applied is a strategy of concentration through horizontal/stability integration. And the strategy that needs to be recommended to the Denpasar Branch of Ikan Bakar Cianjur Restaurant is to use the existing opportunities and strengths, including maintaining a restaurant business culture that has an open and spacious place.